2003
DOI: 10.1103/physreve.68.026307
|View full text |Cite
|
Sign up to set email alerts
|

Intermittency of velocity fluctuations in turbulent thermal convection

Abstract: We analyze velocity fluctuations in turbulent Rayleigh-Bénard convection. The velocity measurements were taken at the center of an aspect-ratio-one convection cell filled with water. The measured probability density functions of the velocity difference over a time interval tau are found to change with tau, indicating that the velocity fluctuations are intermittent. The velocity intermittency can be well characterized by the She-Leveque hierarchical structure. Our analyses further show that the vertical velocit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Using experimental data of Libchaber at the University of Chicago [25,26], Ching and Kwok [27] found that local temperature dissipation in high Rayleigh number convection satisfy a similar SL hierarchy, and Ching [28] showed that the scaling behavior of the temperature structure functions for length scales below and above the Bolgiano scale are both well described by the SL hierarchical symmetry. Both velocity fluctuations [29] and temperature fluctuations [30] were confirmed to be welldescribed by the SL hierarchical symmetry. Xia et al [31] made a direct multipoint measurements of the velocity and temperature fields, and showed that in the central region, velocity and temperature both have excellent SL scaling with different model parameters.…”
Section: Experimental Verifications Of the Hierarchical Symmetrymentioning
confidence: 74%
“…Using experimental data of Libchaber at the University of Chicago [25,26], Ching and Kwok [27] found that local temperature dissipation in high Rayleigh number convection satisfy a similar SL hierarchy, and Ching [28] showed that the scaling behavior of the temperature structure functions for length scales below and above the Bolgiano scale are both well described by the SL hierarchical symmetry. Both velocity fluctuations [29] and temperature fluctuations [30] were confirmed to be welldescribed by the SL hierarchical symmetry. Xia et al [31] made a direct multipoint measurements of the velocity and temperature fields, and showed that in the central region, velocity and temperature both have excellent SL scaling with different model parameters.…”
Section: Experimental Verifications Of the Hierarchical Symmetrymentioning
confidence: 74%
“…The method, plotting (logarithms of) SFs of different orders p against each other and not against the scale r, is usually effective in revealing mutual scaling relations and in particular intermittency. In the context of RB convection, it has first been applied by Benzi et al (1994) and later by Cioni et al (1995), Ching (2000), Zhou & Xia (2001), Skrbek et al (2002), Ching et al (2003b), and Kunnen et al (2008). Independent of the scaling of the second-order velocity SF (K41, BO59, shear flow scaling), dimensional scaling implies S ( p) u (r) ∼ (S (2) u (r)) p/2 .…”
Section: Further Obstacles In Identifying Bo59 Scalingmentioning
confidence: 98%
“…It was found that the two horizontal velocity components are characterized by the same value of β but the vertical velocity component is characterized by a smaller value of β. This distinction was attributed [10] to the presence of the plumes which makes the vertical velocity component more intermittent. As a further test of our scheme of plume extraction, we analyze v b (t) at the cell center to check whether its horizontal and vertical components will now be characterized by the same value of β.…”
mentioning
confidence: 99%
“…In a recent study [10], the three velocity components at the cell center were found to possess the She-Leveque hierarchical structure [11]:…”
mentioning
confidence: 99%